Nikah khitbah : an analytical study based on maqasid al-shari'ah /cby Rita Fatimah - Rita Fatimah (Kulliyyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2019)
With the cost of getting married continue to rise, the number of Muslim youths in Malaysia who to opt for less financially taxing form of marriage which is known as nikah khitbah or nikah gantung continues to rise as well. However, the practice has not been intensively studied. The acronym nikah khitbah itself sounds paradoxical to the specialists in the Islamic jurisprudence because khitbah cannot be combined with nikaḥ. Once nikah is solemnized, khitbah ceases to exist. Nevertheless, Malaysian scholars have developed a convergence between the two in the sense that some of the legal obligations of a proper marriages are postponed in this kind of marriage. Nevertheless, they have differed on the nature of such obligations. In this thesis, researcher employs qualitative research to understand marriage and khitbah as the basis to investigate nikah khitbah. The researcher formulates a formal definition of nikah khitbah. The researcher is interested to know whether nikah khitbah can be an alternative solution to solve the problem of the increasing number of zina. By using maqaṣid al-Shari'ah as a means to analyze nikah khitbah, researcher concludes that by properly regulating of the suspended obligations and the agreement, nikah khitbah can be an alternative solution especially for students to get married and prevent themselves from the sin of zina. The suspension of obligation within nikah khitbah consists the suspension of wedding ceremony, cohabitation, and having children. The agreement of both families to suspend these obligations shall be written in a formal agreement to avoid dispute in the event of separation. This alternative solution can be adopted globally with slight modification according the local custom.